Theological foundations of the new evangelisation - Fisichella, Rino (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
This conference answers to the following question: what does new evangelisation means? The author indicates the biblical foundations of this concept, makes clear its content in the light of Heb 13,8 and thinks about its method (cf. 1Pe 3,15-16), proposing finally an anthropologic perspective (GS 22).
Keywords: gospel; faith; anthropology; apologetics